Visions and Revisions in Sanskrit Narrative: Studies in the Sanskrit Epics and Purāṇas - Balkaran, Raj; Taylor, McComas (Asian Studies Series, 2023)
Sanskrit narrative is the lifeblood of Indian culture, encapsulating and perpetuating insights and values central to Indian thought and practice. This volume brings together eighteen of the foremost scholars across the globe, who, in an unprecedented collaboration, accord these texts the integrity and dignity they deserve. The last time this was attempted, on a much smaller scale, was a generation ago, with Purāṇa Perennis (1993). The pre-eminent contributors to this landmark collection use novel methods and theory to meaningfully engage Sanskrit narrative texts, showcasing the state of contemporary scholarship on the Sanskrit epics and purāṇas